2018
DOI: 10.1162/jinh_a_01231
|View full text |Cite
|
Sign up to set email alerts
|

The Socio-Institutional Divide: Explaining Italy’s Long-Term Regional Differences

Abstract: The recent availability of more accurate estimates of regional gdp, of social indicators (human capital, life expectancy, the human development index [hdi], heights, inequality, and social capital), and of other indices (such as market potential) has helped to advance the study of the growth patterns within Italian regions from (approximately) unification to the present day. This up-to-date information provides the basis for a new explanation of Italy’s industrial expansion and economic growth: The North–South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…The logistic regression model has also discovered a more than double risk of verbal violence in the EDs of the islands and southern Italy. This might be explained, at least in part, by the different organisation of EDs in this geographic area (where understaffing is often frequent, and patient/nurse ratios are high) (Ramacciati, Lumini, Mezzetti, Gili, & Rasero, ), as well as by the socio‐economic imbalance between southern and northern Italy (Felice, ), with higher unemployment, social problems, early school dropout rate and poverty in the south (Istat, 2017a), and partially, based on data from Istat the Italian National Statistical Institute, on crime rates. Although variable and patchy throughout Italy, crime rates are higher in the south for murders and threats (while personal‐injuries are higher in the north, and there are no regional differences for verbal abuse) (Istat, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…The logistic regression model has also discovered a more than double risk of verbal violence in the EDs of the islands and southern Italy. This might be explained, at least in part, by the different organisation of EDs in this geographic area (where understaffing is often frequent, and patient/nurse ratios are high) (Ramacciati, Lumini, Mezzetti, Gili, & Rasero, ), as well as by the socio‐economic imbalance between southern and northern Italy (Felice, ), with higher unemployment, social problems, early school dropout rate and poverty in the south (Istat, 2017a), and partially, based on data from Istat the Italian National Statistical Institute, on crime rates. Although variable and patchy throughout Italy, crime rates are higher in the south for murders and threats (while personal‐injuries are higher in the north, and there are no regional differences for verbal abuse) (Istat, 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no longer any differentiation between regional increases, and the gap between the regions remains constant (frozen). The studies of Boltho et al (), Brunello et al (), Faini (), Felice (, ), Paci and Saba () confirmed this. Conscious theoretical analysis is to be carried out. Authors such as Felice or Sinn have presented the phenomenon empirically.…”
Section: Introductionmentioning
confidence: 69%
“…In the first period from 1871 to 1911, there was a slight divergence. From 1891, this phenomenon accelerated in times of globalization until 1911 (Daniele et al, , p. 644; Felice, , p. 933; Felice, , p. 269; Felice, , p. 44). This was due to regional wage differences between the regions.…”
Section: Historical Development Of Italymentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent issue in southern Italy is its inability to attract businesses and therefore to create jobs. In recent years there have been major advances in the research on patterns of local inequality and their historical roots (Felice, 2018). In this context, new and more accurate estimates of the average equivalized income for the LLSs can be of high interest for policy makers and inspire ad hoc interventions and investments, aiming to reduce territorial inequalities.…”
Section: Italian 2001 Census and 2006 European Union Survey On Incomementioning
confidence: 99%